Capacity limitation based local flexibility market for congestion management in distribution networks: Design and challenges - Nima Mirzaei Alavijeh; David Steen; Anh Tuan Le; Sofia Nyström (International Journal of Electrical Power & Energy Systems)
In this paper, five of the main design challenges of local flexibility markets (LFMs) for congestion management are identified and discussed based on desirable market properties from economics theory and literature review. The five main design challenges are low market liquidity, reliability, baselines, forecast errors at low aggregation levels, and the high cost of measurements. A comprehensive capacity-limitation based LFM design has been proposed to address the challenges and a simulation example is presented to illustrate the design. The proposed design facilitates market participants’ decision making by design elements that improve market liquidity, reliability and handling of forecast errors. Moreover, a new capacity limitation product is proposed that is not defined with respect to a baseline and does not require sub-meter measurements leading to lower costs and conflict-of-interest in delivery validation. Generic algorithms are also proposed for calculating utility and cost of the flexibility product. The proposed design and discussions can contribute to improving the inter-disciplinary area between engineering and economics while helping policy-makers and LFM stakeholders to further understand the problem from a multi-dimensional perspective.